Altruistic Punishment: A Consumer Response to Service Failure. Issue 4 (2nd October 2017) - Silva, Renata Gonçalves Santos; Broilo, Patricia Liebesny; Espartel, Lélis Balestrin; Basso, Kenny
Abstract : Despite the efforts of organizations to perform their services properly, being able to eliminate all possible errors is highly improbable. When service failures occur, they tend to involve some level of social conflict, which in theory can lead to altruistic punishment; however, such behaviors have yet to be explored in relation to such a scenario. This study investigates altruistic punishment from consumers in contexts of service recovery. Two experiments were conducted by adapting the structure of the Ultimatum Game to consumer situations. It was possible to identify altruistic punishment through perceptions of injustice in the form of a rejection of a company's proposal for recovery combined with retaliation. From the findings, it is evident that attention to altruistic punishment in a consumption scenario is advisable, as its occurrence is costly for consumers and businesses.